2007
DOI: 10.1175/waf1033.1
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Heavy Rainfall Occurrences in Taiwan

Abstract: The seasonal variations of heavy rainfall days over Taiwan are analyzed using 6-yr (1997-2002) hourly rainfall data from about 360 rainfall stations, including high-spatial-resolution Automatic Rainfall and Meteorological Telemetry System stations and 25 conventional stations. The seasonal variations and spatial variations of nontyphoon and typhoon heavy rainfall occurrences (i.e., the number of rainfall stations with rainfall rate Ͼ15 mm h Ϫ1 and daily accumulation Ͼ50 mm) are also analyzed. From mid-May to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 25 publications
(56 reference statements)
4
50
0
Order By: Relevance
“…A 'single heavy rainfall' event is when the rainfall exceeds 75 mm at a single station and a 'single very heavy rainfall event' when the rainfall at a single station exceeds 115 mm. This value is close to the 125 mm used by Bradley and Smith (1994) and the 130 mm used by Chen et al (2007).…”
Section: Defining Heavy Rainfallsupporting
confidence: 88%
See 1 more Smart Citation
“…A 'single heavy rainfall' event is when the rainfall exceeds 75 mm at a single station and a 'single very heavy rainfall event' when the rainfall at a single station exceeds 115 mm. This value is close to the 125 mm used by Bradley and Smith (1994) and the 130 mm used by Chen et al (2007).…”
Section: Defining Heavy Rainfallsupporting
confidence: 88%
“…They also concluded that most of these events (66%) are associated with mesoscale convective systems while synoptic and tropical systems play a larger role in the south and east. Chen et al (2007) used a similar statistical approach to investigate heavy rainfall in Taiwan. They found that heavy rainfall occurs with a pronounced afternoon maximum over Taiwan and that the orographic effects are important in determining the spatial distribution of heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, heavy rainfall events caused by TCs were defined as days in which the daily rainfall amount exceeded 50 mm day −1 (TC_R50). In fact, 50 mm day −1 is the heavy rainfall threshold currently used by the forecasters of the National Center for Hydro-Meteorological Forecasting of Vietnam, similar to the criteria of the Central Weather Bureau of Taiwan (Chen et al 2007). TC_R50 ratio was defined as TC_R50 divided by the total heavy rainfall days (the sum of TC_R50 and non TC_R50).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall data comes from the 250 ARMTS stations over the island (Chen et al, 2007). Radar reflectivity with 7.5 min time interval and 1 km x 1 km spatial resolution is from CWB's Chi-Gu Doppler radar (Fig.…”
Section: Data Characteristicsmentioning
confidence: 99%